Aerobic Exercise Improves Methamphetamine-Induced Olfactory Dysfunction Through α-Synuclein Intervention in Male Mice - Wang, Zhuo; Zheng, Rui; Wang, Xiaohan; Huang, Xuekun; Huang, Jian; Gu, Cihang; He, Yitong; Wu, Shuo; Chen, Jingyuan; Yang, Qintai; Qiu, Pingming (Frontiers in Molecular Neuroscience, 2022)
Methamphetamine (Meth) is a predominantly abused neurostimulant, and its abuse is often associated with multiple neurological symptoms. Olfaction, the sense of smell, is a highly neurotransmission-dependent physiological process; however, the effect of Meth on olfactory function and its underlying mechanisms remain largely unknown. This study aimed to explore the impact of Meth abuse on the olfactory system and the potential mechanisms. Chronic Meth abuse was induced by daily administration of Meth in male mice for 4 weeks, and we then systematically examined olfactory performance. Behavioral tests found that Meth-treated animals showed increased olfactory threshold, decreased olfactory sensitivity, reduced olfactory-dependent discrimination, and difficulty in seeking buried food. Notably, the increased deposition of α-synuclein (α-syn) in the olfactory bulb was detected. Adeno-associated virus (AAV)-mediated α-syn intervention therapy in the olfactory bulb significantly alleviated Meth-induced olfactory function impairment, and 8 weeks of aerobic exercise showed similar effects through the same principle of α-syn intervention. Notably, exercise-mediated reduction of α-syn inhibited abnormal firing activity and restored the inhibitory synaptic regulation of mitral cells in the olfactory bulb. These findings suggest the involvement of α-syn in the pathogenic mechanisms of Meth-induced olfactory dysfunction and shed light on the possible therapeutic applications of aerobic exercise in Meth-induced olfactory dysfunction.